Pasteurella (Mannheimia) haemolytica septicemia in an infant: a case report - Warunee Punpanich; Sarunya Srijuntongsiri (Journal of Infection in Developing Countries)
Septicemia due to Pasteurella (Mannheimia) haemolytica is a rare occurrence. We report a fatal case of M. haemolytica septicemia in a seven-month-old infant who presented with prolonged fever, sepsis, and pneumonitis without discernable preceding history of animal bites or contact. Rare cases of systemic Mannheimia infections are reviewed and summarized.